2019
DOI: 10.2337/dc18-2308
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Retinopathy in Type 1 Diabetes: The DCCT/EDIC Study

Abstract: The Diabetes Control and Complications Trial (DCCT) demonstrated that intensive therapy reduced the development and progression of retinopathy in type 1 diabetes (T1D) compared with conventional therapy. The Epidemiology of Diabetes Interventions and Complications (EDIC) study observational follow-up showed persistent benefits. In addition to glycemia, we now examine other potential retinopathy risk factors (modifiable and nonmodifiable) over more than 30 years of follow-up in DCCT/EDIC. RESEARCH DESIGN AND ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
81
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(94 citation statements)
references
References 22 publications
10
81
0
3
Order By: Relevance
“…DCCT-EDIC studies have shown that institution of early intensive therapy lowers the incidence of further progression of retinopathy, and even 30 years after the start of DCCT, former intensive therapy participants still report better Visual Function than the former conventional group 33 . Animal models have also demonstrated that institution of good glycemic control, soon after establishment of diabetes, prevents impairments in mitochondrial biogenesis, and the development of retinopathy 15,17 .…”
Section: Discussionmentioning
confidence: 98%
“…DCCT-EDIC studies have shown that institution of early intensive therapy lowers the incidence of further progression of retinopathy, and even 30 years after the start of DCCT, former intensive therapy participants still report better Visual Function than the former conventional group 33 . Animal models have also demonstrated that institution of good glycemic control, soon after establishment of diabetes, prevents impairments in mitochondrial biogenesis, and the development of retinopathy 15,17 .…”
Section: Discussionmentioning
confidence: 98%
“…The regressions’ R 2 values were used to describe the proportion of the variance of a body composition measure that is explained by an anthropometric measure. The relevance ranking of each variable was based on the z statistics allowing comparisons across risk factors independently of their measurement units 38 . WHR and WHtR were scaled by a factor of 10.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we investigated DNAm age calculated by all four methods in 499 subjects with T1D from the Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications (DCCT/EDIC) study and its association with diabetic complications (CVD, nephropathy, retinopathy, and neuropathy) and their risk factors [14][15][16]. We also examined DNAm age in a smaller subset at two time points, 16-17 years apart, to investigate changes in DNAm age over time.…”
Section: Introductionmentioning
confidence: 99%